Help relationship through history: a contribution from an iconographic perspective - Mercedes Núñez del Castillo; José Siles González; José Luis Jurado Moyano (Cultura de los Cuidados, 2012)
Henderson’s need to communicate with other people to express emotions, needs, fears or opinions, constitutes the essential basis of help relationship (Rogers, 1986); this help relationship although it might be adapted in a paramount way to nursing care, could not always be totally transferred to those nursing cares. In order to identify help relationship along history, many sources have been used, being iconography one of them. The iconographic material to be used to verify or invalidate hypothesis is as much of a civil character as of a religious one, obtained by data collected from the National Prado Museum, Madrid Archeological National Museum, and the Cave Paintings around the Mediterranean area, in the Spanish Peninsula. Variables have been distributed in categories according to the characteristics of the so called help relationship. For the purpose of this test, the iconographic interpretation proposed by Panofsky (1995) as well as Siles’s diagrams (1999) have been used. The most ancient iconographies where help relashionship appears are from XI century and the most recent ones are from XIX century. 6 are from a religious origin and 6 from civil origin. As a final outcome there could be said, that in relationship verbal or no-verbal communication exists, and that the care taker is always informal.